(3GdTQhW hGdGLQGAGJ GdSGHbI Ydi Yed GdSdWI GdeJYGbOI hGKGQgG Ydi YbhO GdGOGQI (B: s (3OQGSI ebGQfI (B/ s - (3eUWai cGed eMeO Ydjs; (3eMehO YGWa GdHfGs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3bGeJ GdOQGSI Ydi GSGS GJHGY GdefgL GdJMdjdi GdJGUjdi eY GdJYeb (B: (3hPdc HJMdjd hJGUjd GdTQhW hGdGLQGAGJ GdSGHbI Ydi Yed GdSdWI GdeJYGbOI (B: (3HHjGf eGgjJgG hGfhGYgG hGdhbha Ydi WHjYJgG GdbGfhfjI hGdfJGFL GdeJQJHI Ydi gPg GdWHjYIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdYGe, (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B563-588s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdGYJeGOGJ GdeGdjIs; (3GdbGfhf GdEOGQj hGdeGdjs; (3EHQGe YbhO GdEOGQIs; (3GdfJGFL GdeJQJHI ddGYJeGO GdeGdjs; (3GdJUQjM HGdJYGbOs; (3GdJcjja GdbGfhf ddJUQjM HGdJYGbOs; (3YbO GdHhJs; (3BKGQ GdJUQjM dYbhO GdEOGQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes